2020
DOI: 10.4314/ejhs.v30i6.21
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives of Protocol Based Breaking Bad News among Medical Patients and Physicians in a Teaching Hospital, Ethiopia

Abstract: BACKGROUND፡ Discussing potentially bad outcomes is a standard communication task in clinical care. Physicians’ awareness on ways to communicate bad news is considered low. SPIKES protocol is the most popular strategy used by physicians, but its practice and patients' perception are not known. This study attempted to fill the knowledge gap on protocol implementation, patient preference and physician effects.METHODS: Hospital-based descriptive cross-sectional study was conducted at SPHMMC from May 1 to June 30 u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 22 publications
(61 reference statements)
3
10
0
3
Order By: Relevance
“…Alnefaie et al from Saudi Arabia reported that 38.3% of surgeons in academic hospitals were aware of the SPIKES protocol. Only 20% had received specific training courses, while most of them agreed on the necessity of improving their communication skills Fisseha et al from Ethiopia discussed that the SPIKES protocol was poorly implemented, and only 30.6% of patients were delighted with the physicians' communication [25]. As mentioned above, the results of studies in different areas are contradictory.…”
Section: Discussionmentioning
confidence: 99%
“…Alnefaie et al from Saudi Arabia reported that 38.3% of surgeons in academic hospitals were aware of the SPIKES protocol. Only 20% had received specific training courses, while most of them agreed on the necessity of improving their communication skills Fisseha et al from Ethiopia discussed that the SPIKES protocol was poorly implemented, and only 30.6% of patients were delighted with the physicians' communication [25]. As mentioned above, the results of studies in different areas are contradictory.…”
Section: Discussionmentioning
confidence: 99%
“…Among the existing communication protocols for conveying bad news, SPIKES is one of the most popular worldwide 11 . In the literature, the greater prominence of SPIKES is justified by its flexibility 12 .…”
Section: Medical Knowledge Of Protocols and Other Strategies Used To ...mentioning
confidence: 99%
“…Regarding In fact, studies carried out in different countries disclose a lack of training during academic formation, which explains many of the problems reported by health professionals 9,11,15 .…”
Section: Academic Training On the Communication Of Bad Newsmentioning
confidence: 99%
“…Dentre os protocolos de comunicação de más notícias existentes, o SPIKES é um dos mais populares em todo o mundo 11 .…”
Section: Conhecimento Médico Sobre Protocolos E Outras Estratégias Ut...unclassified
“…De fato, estudos realizados em diferentes países revelam uma insuficiência de treinamentos durante a formação acadêmica, o que explica muitos dos problemas relatados pelos profissionais de saúde 9,11,15 . No Brasil, uma pesquisa recente, com 162 escolas médicas, constatou o ensino da comunicação de más notícias em apenas 41 delas 16 .…”
Section: Conhecer Algum Protocolo] Principalmente Quando Você Não é E...unclassified